DESIGN AND IMPLEMENTATION OF MOBILE LEARNING WITH RASE FRAMEWORK: APPLYING TO THE BALANCE OF RIGID BODIES - Mubasir, Yazid; Hardyanto, Wahyu; Supriyadi, Supriyadi (Universitas Negeri Semarang, 2018)
This study aims to produce mobile learning applications with RASE framework on android platform that can be used as a tool of learning physics class XI on the subject of balance of rigid body. In addition to know the perception of learners to the media developed in terms of compliance with usability standards and mobile quality. This research is a research R & D with design include: requirement analysis, product planning and development, product development, product evaluation, final product, dissemination and presentation. The developed application named amolef has been implemented in 93 students of class XI Senior High School 3 Purworejo. Data collection is done by giving validation sheet to expert lecturer. Questionnaire response of learners has also been given to give input to the developed product. The results showed that the product of development result was declared viable based on expert assessment and response of the students with very good category. Through one sample t-test the characteristics of media meet usability and mobile quality standards. Implementation in the study of physics on the subject of balance of rigid body able to improve student performance.